Advances and strategies for capillary electrophoresis in the characterization of traditional Chinese medicine: A review of the past decade (2011–2021) - Shamsi, Shahab A.; Patel, Jalpaben (Frontiers in Analytical Science, 2023)
While traditional Chinese medicine (TCM) is considered a valuable resource for drug discovery and form a potential basis for drug development, they also carry substantial safety risks due to adverse drug reactions and a lack of understanding of their mechanisms of action. However, due to their highly complex composition, valid analytical methodologies for analyzing TCMs must be developed and promoted. An extensive search of published research and review of scientific papers implies that the increased efficiency and sensitivity of capillary electrophoresis (CE) has attracted much research attention. This review provides an in-depth assessment of CE applications for TCM analysis published in the open literature in the last decade (2011–2021). Our survey findings showed that capillary zone electrophoresis (CZE) with ultraviolet (UV) detection is a capillary electromigration technique frequently utilized for the efficient separation, identification, and quantitation of various active components in highly complex matrices. Different extraction methods, modifiers to the background electrolyte, preconcentration techniques, and mass spectrometry (MS) detectors are used to enhance CE separation selectivity and TCM sensitivity.